Increasing Temperature and Microplastic Fibers Jointly Influence Soil Aggregation by Saprobic Fungi - Liang, Yun; Lehmann, Anika; Ballhausen, Max-Bernhard; Muller, Ludo; Rillig, Matthias C. (Frontiers in Microbiology, 2019)
Microplastic pollution and global warming are two aspects of global change that potentially influence soil quality; yet little is known about their effects on soil aggregation, a key determinant of soil quality. Given the importance of fungi for soil aggregation, we investigated the impacts of rising temperature and microplastic fibers on aggregation by carrying out a soil incubation experiment in which we inoculated soil individually with specific strains of soil saprobic fungi (Chaetomium elatum, Truncatella angustata, Fusarium redolens, Mucor fragilis, and Fusarium sp.). Our treatments were temperature (ambient temperature of 25℃ or temperature increased by 3℃, abruptly versus gradually) and microplastic fibers (control and 0.4% w/ w). We evaluated the percentage of water stable aggregates (WSA) and hydrolysis of fluorescein diacetate (FDA). Microplastic fiber addition was the main factor influencing the WSA, decreasing the percentage of WSA except in soil incubated with M. fragilis, and mitigated the effects of temperature or even caused more pronounced decrease in WSA under elevated temperature. We also observed clear differences between temperature change patterns. Our study shows that the interactive effects of warming and microplastic fibers are important to consider when evaluating effects of global change on soil aggregation and potentially other soil processes.